Evaluating HEDPERF as Predictor of Business Students' Satisfaction in the Provision of Quality Education Services (Global Journal of Human-Social Science, 2019)
The pressure for modification of higher education sector can be traced globally.The study aimed to assess service quality provided by University for Development Studies School of Business and Law (UDS-SBL) in the opinion of business students via HEdPERF service quality model.Literature was reviewed to cover: higher education and service quality, higher education performance model (HEdPERF), the relationship between service quality and students' satisfaction, and students' satisfaction. The research approach was quantitative and the design was descriptive. As a quantitative study, a questionnaire with close ended questions was used to elicit the responses. It was found that the association between service quality variables and general business students' satisfaction were vastly significant, with programmes aspects being the strongest. Meanwhile, academic, non-academic, reputation, access and design aspects are equally paramount and should be given special attention.
Keywords: hedperf; business students; satisfaction; quality; education; service quality